Low-cost rolling ball viscometer for the evaluation of Newtonian and shear-thinning fluids - Diañez Isabel; Martínez Inmaculada; Jerez Abel; Franco José M. (Applied Rheology)
This article describes the design and testing of a low-cost automatic rolling-ball viscometer. The device has been manufactured from three-dimensional printed parts and conventional and affordable mechanical and electronic components. It is controlled by an Arduino MEGA with a custom code that includes manual and automatic measuring modes. Both the type of viscometer and the models used are, in principle, valid for Newtonian and power-law fluids. However, measurement and calculation procedures have been developed that also makes it possible to determine the viscosity of Herschel–Bulkley fluids that might exhibit a yield stress behaviour within the range studied. By these procedures, viscosity values have been obtained for model fluids – Newtonian, power-law, and Herschel–Bulkley fluids – and compared to those obtained with a commercial rotational rheometer. The proposed setup and measuring method have thus proven to provide very reasonably accurate viscosity values for a low-cost device.